CONTRIBUTION TO THE PHYTOMEDICINAL STUDY OF THE SOLID AND AQUEOUS EXTRACT OF Anthurium schlechtendalii KUNTH ROOT AGAINST LIVER DAMAGE IN A RAT MODEL - Barradas, Dermitz; Dulce, maría; Nolasco-Hipolito, Cirilo; Hayward, Jones; Patricia, Margaret; Ramírez, Hemández Aurelio; Calderon, Garcidueñas; Ana, Laura; Olaide, Olawunmi Ajibola; Carvajal Zarrabal, Octavio (SILAE - Societa Italo-Latinoamericana di Etnomedicina, 2021)
Plants have been used as a herbal treatment option for liver disease in alternative medicine. The current study was carried out to investigate the therapeutic potential of Anthurium schlechtendalii Kunth roots as a hepatoprotective or remission agent for liver damage. A preclinical study was carried out through oral administration of 4-tert-octylphenol (100 mg kg-1/day) as inducer of liver disease, and solid and aqueous extracts from the plant roots. The extracts were tested at doses of 125 mg kg-1/day and 1.8 mg mL-1/day, respectively, using a rat model in a 4-week experiment. Growth parameters (initial and final body weight, food intake, liquid consumption, liver weight) and liver function markers (aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP) were determined. In addition, analysis of variance (one-way ANOVA) procedures, with a post hoc Tukey’s multiple range test for comparison of means (p <0.05), were performed. The study showed that, according to the lethal concentration (LC50) through the PROBIT transformation, the extract was nontoxic. The experimental model used, however, was not able to show liver function marker damage nor changes in growth parameters, so no statistically different results were found between the study groups (A, control; B, 4-tert-octylphenol; C, solid extract; D, solid and aqueous extracts; E, 4-tertoctylphenol plus solid extract; F, 4-tert-octylphenol plus solid and aqueous extracts). The method of toxic administration was not through direct oral dose but mixed in food, possibly producing a low intake of 4-tert-octylphenol thus not causing liver function marker damage. The need to continue and expand relevant research, to accumulate sufficient scientific knowledge and elucidate the efficacy of A.schlechtendalii Kunth roots in the prevention, mitigation, or remission of liver damage, has been made evident by the results obtained.